HAK ASUH ANAK AKIBAT CERAI GUGAT DALAM PERKARA NOMOR 0915/Pdft.G/2017/PA.Bgr - A Arnengsih; Ramdani Wahyu Sururie (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2020)
ABSTRACT This research is motivated by the existence of an Application for Divorce Claims in Bogor Religious Court ruling as an Applicant filing for Claims Divorce and Child Custody. The Plaintiff as a mother filed a lawsuit to the Bogor Religious Court so that Child Custody fell on the Plaintiff. But the Defendant as the father is suing back, that the child custody holder is his father because his mother does not reflect as a good mother. Then the Board of Judges of the Bogor Religious Court rejected the Plaintiff's claim and granted the Defendant's claim to establish custody of the child at the Defendant until the child is 14 years old provided that the plaintiff is given access to meet the child. This study aims to determine the legal basis of the Panel of Judges, the method of finding the Panel of Judges in child custody cases. The results of this study are: 1. The consideration of the panel of judges granted the Defendant's lawsuit because he saw from the facts in the trial and based on the evidence submitted by the parties and looked at the benefit of the child. 2. Judges use the method of legal construction in legal discovery, namely the method of law enforcement (rechtsvervjnings). In this method, the judge can rule out articles that are deemed incompatible with the facts at this time.